(untitled) (Nexo Revista Científica, 2020)
The response of active ingredient, chlorophyll a and b contents, and chlorophyll index of henna to different rates of N fertilization and drought stress was explored in a split-split-plot experiment based on a randomized complete block design with four replications in the research farm of Jiroft Branch, Islamic Azad University, Jiroft, Iran in the 2016-2017 growing season. In the current study, the main plot was assigned to drought stress at three levels (including irrigation to supply 100%, 75% or 50% of plant water requirement), the sub-plot was assigned to N fertilization at three rates (50, 100 or 150 kg ha-1 pure N), and the sub-sub-plot was assigned to ecotype at three levels (Bami, Bushehri, and Rudbari). The results showed that the effect of drought level was significant on active ingredient and chlorophyll index at the p < 0.01 level and on chlorophyll a, total chlorophyll, and chlorophyll a/b ratio at the p < 0.05 level. But, it could not influence chlorophyll b significantly. The effect of N fertilization was significant on most studied traits at the p< 0.01 level, but its effect was significant on the chlorophyll index at the p < 0.05 level and insignificant on dye and chlorophyll b. According to the results, it seems that the application of 100 kg ha-1 N and the irrigation to supply 75% of plant water requirement can contribute to having more fresh plants with the higher active ingredient and dye contents.